2020
DOI: 10.1590/1678-7757-2020-0438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glazing application side and mechanical cycling on the biaxial flexural strength and Weibull characteristics of a Y-TZP ceramic

Abstract: Glaze application on monolithic zirconia (Y-TZP) can be a practical approach to improve the mechanical properties of this material. Objective: Our study evaluated the effect of glazing side and mechanical cycling on the biaxial flexure strength (BFS) of a Y-TZP. Methodology: Eighty sintered Y-TZP discs (Ø:12 mm; thickness: 1.2 mm-ISO 6872) were produced and randomly assigned into eight groups (n=10), according to the factors "glazing side" (control-no glazing; GT-glaze on tensile side; GC-glaze on compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Of note, we used a self-aligning four-point bend jig which ensured that any potential misalignment of a specimen was not exacerbated using a fixed bending jig thereby inducing the failure at an artificially induced high-stress area. In a previous fractographic study, pores were observed in the glaze layer, but these did not seem to initiate fracture [45]. We also observed voids in the glaze layer at the glaze/zirconia interface at the corner of several specimens which may have caused fracture initiation at those sites (Figure 7).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Of note, we used a self-aligning four-point bend jig which ensured that any potential misalignment of a specimen was not exacerbated using a fixed bending jig thereby inducing the failure at an artificially induced high-stress area. In a previous fractographic study, pores were observed in the glaze layer, but these did not seem to initiate fracture [45]. We also observed voids in the glaze layer at the glaze/zirconia interface at the corner of several specimens which may have caused fracture initiation at those sites (Figure 7).…”
Section: Discussionsupporting
confidence: 45%
“…Without clear identification of where the glaze is applied to the specimen, it is difficult to directly compare our results with previous studies. A recent study by Lobo et al reported the effect of glaze application and mechanical ageing on the biaxial flexural strength of Y-TZP and found that glaze applied on both the tensile and compression sides improve the flexural strength of Y-TZP [45]. This study, however, only used a sample size of n = 10 on which to report their Weibull results.…”
Section: Discussionmentioning
confidence: 96%